ANALISIS KUALITAS PERAIRAN DAN EKONOMI MASYARAKAT NELAYAN PADA WILAYAH PENGOLAHAN SAGU DISELAT ASAM DESA MEKARSARI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI - Yusmaida Yusmaida; Syafruddin Nasution; Rahman Karnila (Jurnal Ilmu Lingkungan, 2015)
ABSTRACTThis research was conducted from May to June 2014 in asam strait. Mekarsari Village Merbau sub district Meranti Islands regency. This research aimed to analyze the quality ofthe waters around the disposal of liquid waste of sago processing plantin waters of asam Strait and obtained the economic view of traditional fishermen in Mekarsari village that fishing in the waters of the asam Strait. The method used in this research is a survey method, while to know the economic of fishermen in Mekarsari Village who fishing in the asam Strait, conducted interviews to all of the fishermen that there are 27 people, based on a list of questions that have been made. The result of the study show that some of water quality parameters in the asam Strait of Mekarsari village has exceeded the quality standard based on the Ministry of environmental No.51 of 2004 such as TSS, turbidity, nitrate, ammonia and BOD5. Based on the observations of the macrozoobenthos were found during research in asam Strait of Mekarsari Villages hows that, over all asam strait were moderately polluted with macrozoobenthos diversity index < 3, while the third stations showed heavily polluted conditions with the discovery of macrozoobenthos Capitella sp. Fishermen economic based on the data of fishing income during the study showed greatly a decrease from year to year.